Developing an Ethical Guideline for Making and Using Audiovisual Recordings of Patients in Iran - Mahboobeh Khabaz Mafinejad; Marjan Kouhnavard; Fariba Asghari; Pooneh Salari; Maliheh Kadivar; Alireza Parsapoor; Hessameddin Riahi; Mitra Zolfaghari (Journal of Medical Ethics and History of Medicine)
Introduction: Widespread use of smartphones among health care professionals, and increasing audiovisual recording of patients with the aim of clinical and non-clinical purposes has emerged serious ethical, legal and social issues. To address such issues several guidelines have been developed in many countries. However, providing a practical and easily accessible ethical guideline with respect to national values seems necessary. Therefore, we developed an ethical guideline for making and using audiovisual recordings of patients with special attention to Iranian culture, social principles and Islamic commands. Materials & Methods: This study was conducted at Tehran University of Medical Sciences in 2017-2019 and the guideline was developed through four phases:  Literature review, focused group discussions, Expert panels, Assessing stakeholders’ views. Results: The final draft of this guideline consisted of 43 items of "General Regulations" and 25 items of "Specific Regulations". The "General Regulations Section" covered the considerations before, during and after audiovisual recordings of patients. The "Specific Regulations Section" included ethical principles on audiovisual recordings of children and adolescents, cadavers, and patients with impaired decision making capacity as well as the ethical issues on broadcasting the recordings on public media. Conclusion: Developing an ethical guideline for making and using audiovisual recordings of patients with respect to social, cultural and religious considerations will be helpful to address the emerging ethical, legal and social issues in this regard.